2020
DOI: 10.1161/atvbaha.119.313357
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial BMPR2 Loss Drives a Proliferative Response to BMP (Bone Morphogenetic Protein) 9 via Prolonged Canonical Signaling

Abstract: Objective: Pulmonary arterial hypertension is a disease of proliferative vascular occlusion that is strongly linked to mutations in BMPR2 —the gene encoding the BMPR-II (BMP [bone morphogenetic protein] type II receptor). The endothelial-selective BMPR-II ligand, BMP9, reverses disease in animal models of pulmonary arterial hypertension and suppresses the proliferation of healthy endothelial cells. However, the impact of BMPR2 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…For example, loss of BMP or related TGF-β receptors indirectly affects the abundance of other receptors complexes (Hiepen et al 2019; Lowery et al 2015; Razavi, Lopez, and Lyons 2019). More specifically, BMPR2 knockdown has unexpected and ligand-specific effects across a variety of cell types (Han et al 2013; Hiepen et al 2019; Yu et al 2005; Olsen et al 2018; Theilmann et al 2020), which may be explained by the low predicted activity of BMPR1A-BMPR2 complexes that recurred in all model fits. In pulmonary artery cells and myeloma cells, BMPR2 knockdown either did not affect or decreased signaling by BMP4 and BMP10, while, respectively, increasing or having no effect on signaling by BMP7 and BMP9.…”
Section: Discussionmentioning
confidence: 99%
“…For example, loss of BMP or related TGF-β receptors indirectly affects the abundance of other receptors complexes (Hiepen et al 2019; Lowery et al 2015; Razavi, Lopez, and Lyons 2019). More specifically, BMPR2 knockdown has unexpected and ligand-specific effects across a variety of cell types (Han et al 2013; Hiepen et al 2019; Yu et al 2005; Olsen et al 2018; Theilmann et al 2020), which may be explained by the low predicted activity of BMPR1A-BMPR2 complexes that recurred in all model fits. In pulmonary artery cells and myeloma cells, BMPR2 knockdown either did not affect or decreased signaling by BMP4 and BMP10, while, respectively, increasing or having no effect on signaling by BMP7 and BMP9.…”
Section: Discussionmentioning
confidence: 99%
“…86 Similarly, a BMPRII-dependent shift in the endothelial proliferative response to BMP9 was reported, whereby BMP9 inhibited the proliferation of healthy donors endothelial cells but enhanced the proliferation of endothelial cells from BMPR2 mutation bearing PAH patients. 64 At first glance, these results seem contradictory, however, different strategies have been used (adding exogenous BMP9 vs loss or inhibition of BMP9) that could contribute to different interpretations which have been thoroughly discussed in the editorial from Ormiston et al 114 Together, these data indicate an important role for BMP9 in PAH pathogenesis and underscore that further investigations for the therapeutic use of BMP agonists in PAH are needed before going to PAH patients.…”
Section: Bmp9 and Bmp10 In Therapiesmentioning
confidence: 99%
“…Upon BMP9 or BMP10 binding, the type II receptor will phosphorylate the type I receptor, which will then phosphorylate SMAD1/5/9 within 5 minutes for a period depending on the concentration of BMP9 or BMP10. This period ranges from few hours with low doses (0.1 ng/mL) reaching up to 24 hours with higher doses (10 ng/mL) 7,64 . The complex BMP9/ALK1 is rapidly endocytosed and can then either be recycled to the membrane or degraded by proteolysis 65 .…”
Section: Bmp9 and Bmp10 Receptors And Signalingmentioning
confidence: 99%
“…The studies suggest that the BMP4-MGP balance could serve as a point of influence for factors that affect VC, such as warfarin that interferes with the necessary gamma-carboxylation of the MGP protein (Yao et al, 2008). As the transitioned ECs migrate into the vascular wall, they may be exposed to BMP2, which is highly induced in calcified vascular lesions (Sweatt et al, 2003) and would promote calcification of osteogenic ECs.…”
Section: Endmts In Vascular Calcificationmentioning
confidence: 99%
“…BMP9 signaling is mediated by ALK1 and potentially ALK2 with effects on the endothelial lineage as well as osteoinduction (David et al, 2008;Lamplot et al, 2013). Interestingly, Sanchez-Duffhues et al (2019) showed that the osteoinductive effect could be mitigated by suppressing the BMP type 2 receptor (BMPR2) and JNK signaling (Sanchez-Duffhues et al, 2019), andTheilmann et al (2020) showed that loss of BMPR2 drove a proliferative response to BMP9 in EC, which is a reversal of the usually response promoting cell maturation. Thus, the outcome of BMP9 signaling is likely to vary depending on the on the state of BMPR2 and downstream signaling.…”
Section: Aortic Induction Of Alk1 Might Facilitate Bmp9-mediated Osteoinductionmentioning
confidence: 99%